Public Interest Environmental Litigation: A Comparative Study of Locus Standi Requirements in South Africa and Zambia - Mulenga, Martin (School For Advanced Legal Studies, 2023)
South Africa integrated environmental rights into its constitutional and legislative framework, and simultaneously expanded its locus standi rules that facilitated public interest environmental litigation a decade and a half earlier than Zambia. The incorporation of environmental rights and the liberalisation of legal standing requirements occurred in South Africa with the enactment of the interim democratic constitution of 1994 which eventually progressed into the final constitution of 1996. Zambia only legislated environmental rights and liberalised the locus standi rules in environmental litigation with the enactment of the Environmental Management Act of 2011. The Zambian constitution has not yet included environmental rights in its Bill of Rights, but it has incorporated many internationally recognised environmental principles which may become building blocks for the further entrenchment and enhancement of environmental rights. The purpose of this paper is to conduct a critical and comparative analysis of the South African and Zambian legal frameworks with regard to locus standi requirements in public interest environmental litigation. The objective is to appreciate the strides that South Africa has made in public interest environmental litigation by critically assessing the constitutional and legislative developments that have taken place in that jurisdiction with a view to drawing lessons for Zambia. Included in the critical analysis is a study of how the South Africa Judiciary has interpreted these legislative developments and implemented them in its judgments particularly with regard to legal standing requirements. The comparison is intended to identify challenges to and opportunities for public interest environmental litigation in Zambia.